Current PROM and PREM use in health system performance measurement: Still a way to go - Claudia Bull; Emily Callander (The Beryl Institute, 2022)
There is a growing impetus to "measure what matters" to enable health systems to optimise value-based, person-centred healthcare. This paper describes the critical importance of patient-reported outcome and experience measures (PROMs and PREMs) in this pursuit and provides an in-depth overview of how PROM and PREM programs differ between England, the United States, and Australia. A comprehensive timeline of PROM, PREM, legislation/policy, and value-based purchasing (pay-for-performance) program implementation accompanies this discussion. Importantly, this paper highlights disparities between these nations' PROMs and PREMs programs, evidencing that we still have a way to go towards equal health system performance measurement globally. Experience Framework This article is associated with the Policy & Measurement lens of The Beryl Institute Experience Framework. (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Policy%20%26%20Measurement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.